Acute and transient psychotic disorder (ATPD) in a developing country (2014)
Background: Acute and transient psychotic disorders (ATPDs) are relatively under-researched. There is therefore a dearth of information on the disorders especially in developing countries, where they have been shown to be relatively common. Aim: To describe the socio-demographic and clinical characteristics of patients with ATPD, as well as to examine the factors that are associated with early recovery in patients with ATPD in a developing country. Methods: A review of 124 cases of untreated first episode of ATPD that presented at the University College Hospital, Ibadan, Nigeria over a five-year period. Results: Of the new cases that presented at the psychiatry department of the hospital, 10.1% were ATPDs. There was no significant difference between the proportions of males and females presenting at the hospital (50.8% vs 49.2%). Mean age at presentation was 29.5 (SD = 9.6) years, while the mean duration of illness before presentation was 7.3 (SD = 6.1) days. Female gender was significantly associated with earlier recovery (p= .047). Conclusion: ATPDs are common in developing countries. The epidemiology in developing countries is probably different from that of the developed countries.